Evaluation of the Quality of Human Resources in the Regional Bureaucracy in Ponorogo Regency - Widiyahseno, Bambang; Okolie, Ugo Chuks; Arviana, Ekyk; N, Moh Uzma; Ridho, Guruh; Hilman, Yusuf Adam (Jurnal Studi Ilmu Pemerintahan, 2024)
The problem of bureaucracy is a challenge that must be addressed by the government. Improving the local government bureaucracy is a very important effort to be made because in the bureaucracy there are various aspects that can support the implementation of the public service process, one of which is the human resources aspect. The purpose of this paper is to find out how the evaluation and form of reform carried out by the Ponorogo Regency Regional Government on the human resources of its government bureaucracy. The method used in this writing is a qualitative method with a case study on one of the bureaucratic phenomena in Ponorogo Regency. The writing data is obtained through journal articles obtained through websites. Data analysis was conducted using literature studies based on relevant theories and references. The results of the discussion found that several aspects of assessing the performance evaluation of the Regional Apparatus Organisation of Ponorogo Regency include: a) Performance planning; b) Performance measurement; c) Performance reporting; d) Performance evaluation; and e) Performance achievement. Performance achievement. In addition, the bureaucratic reform carried out by the Regional Government of Ponorogo Regency prioritises three main goals, namely: a) A clean and accountable bureaucracy; b) An effective and efficient bureaucracy; and c) A bureaucracy that has quality public services.